2003
DOI: 10.1002/jbm.a.10143
|View full text |Cite
|
Sign up to set email alerts
|

Direct attachment of fibronectin to tresyl chloride‐activated titanium

Abstract: The aim of this study was to bind fibronectin directly to a titanium surface treated with tresyl chloride (2,2,2-trifluoroethanesulfonyl chloride) for the development of a strong connection of a dental implant to subepithelial connective tissues and/or peri-implant epithelia. Basic terminal OH groups of mirror polished titanium were allowed to react with tresyl chloride at 37 degrees C for 2 days. The tresylated titanium disk was then immersed into a fibronectin/phosphate-buffered saline solution for 24 h at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 22 publications
2
55
1
Order By: Relevance
“…(34)(35)(36)(37) Biomimetic coating with fibronectin has been tested in previous studies, (20)(21)(22)(23) its adsorption onto solid substrates has already been evaluated in previous studies, though the interactions between this protein and biomaterial surfaces are not fully understood. (30,38) Although many studies reported about the applications of fibronectin to the implant surface can enhance the osseointegration of dental implants to the bone, (39,40) the results of the present study demonstrating the difference between two groups was not statistically significant at both observation periods and this could be due to:…”
Section: Discussioncontrasting
confidence: 52%
“…(34)(35)(36)(37) Biomimetic coating with fibronectin has been tested in previous studies, (20)(21)(22)(23) its adsorption onto solid substrates has already been evaluated in previous studies, though the interactions between this protein and biomaterial surfaces are not fully understood. (30,38) Although many studies reported about the applications of fibronectin to the implant surface can enhance the osseointegration of dental implants to the bone, (39,40) the results of the present study demonstrating the difference between two groups was not statistically significant at both observation periods and this could be due to:…”
Section: Discussioncontrasting
confidence: 52%
“…1: Uncoated; 2: GRGDSP-coated. 10) . Studies have shown that RGD and related peptides are able to enhance osteoblast adhesion and migration 11,12) .…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic peptides were coated on Ti surfaces using the tresyl chloride activation method described in previous literature 10) . Briefly, Ti disks (JIS, Japan industrial Specification H 4600, 99.9 mass% Ti; Furuuchi Chemical Corp., Tokyo, Japan) with a diameter of 15 mm or 48 mm were used.…”
Section: Peptide Coating Onto Ti Disksmentioning
confidence: 99%
“…Collagen was immobilized onto 1.0 Laser-Ti implants by the tresyl chloride-activated method 19,20) . This immobilization scheme is shown in Fig.…”
Section: Immobilization Of Collagen With the Tresyl Chloride-activatementioning
confidence: 99%